HEAT TRANSFER ANALYSIS IN THE HIGH PRESSURE HEATER CFB BOILER OF PLTU TELUK SIRIH UNIT 2 - Muhammad Anwar; Mukhnizar , Mukhnizar; Risal Abu (Ikatan Dosen Menulis, 2025)
Teluk Sirih Steam Power Plant (PLTU) is a coal-fired power plant with a capacity of 2 × 112 MW, utilizing a Circulating Fluidized Bed (CFB) boiler. One of the critical components in this system is the High Pressure Heater (HPH), which functions as a feedwater preheater to improve the thermal efficiency of the cycle. This research aims to analyze the heat transfer performance of HPH 1 and HPH 2, and to identify the factors contributing to the efficiency decline. The analysis methods include calculations of Terminal Temperature Difference (TTD), Drain Cooler Approach (DCA), Temperature Rise (TR), Log Mean Temperature Difference (LMTD), Heat Capacity Ratio, and thermal effectiveness (ε). Data were collected from performance tests conducted in 2024 and compared with commissioning data from 2014. The results indicate a performance degradation in the HPH units, as shown by increased TTD and DCA values and decreased effectiveness. This decline is suspected to be caused by fouling or damage to the heat exchange tubes, which adversely affects water heating efficiency. The study recommends regular maintenance and cleaning measures to restore the performance of the HPH units. This research is expected to contribute to improving plant efficiency and reducing fuel consumption.